The ruby circle : a Bloodlines novel - Mead, Richelle (Mead, Richelle. Bloodlines novel., 2015)
With their romance exposed, Sydney and Adrian face the wrath of the Alchemists and the Moroi alike as Sydney hunts down a former nemesis and Adrian discovers a secret about spirit magic.